Expression of 5-HT receptors and the 5-HT transporter in rat brain after electroconvulsive shock. - Burnet, P; Sharp, T; LeCorre, S; Harrison, P (1999)
Modulation of central 5-HT receptor sensitivity is implicated in the therapeutic response to electroconvulsive shock (ECS). Altered 5-HT receptor expression may play a role in this process. We have measured the mRNAs encoding 5-HT1A, 5-HT2A, 5-HT2C and 5-HT7 receptors, and the 5-HT transporter, in rat brain after single ECS, repeated ECS, and 3 weeks after repeated ECS. Hippocampal 5-HT1A receptor mRNA was decreased in CA4 and increased in dentate gyrus by single or repeated ECS, with parallel alterations in [3H]8-OH-DPAT binding site densities. Repeated ECS increased cortical [3H]ketanserin binding and 5-HT2A receptor mRNA. The other mRNAs were unchanged. The results show that ECS has subtype specific, anatomically discrete, and temporally selective effects on 5-HT receptor expression.